A radiographic study of joint angles in standing dogs - Milgram, J.; Slonim, E.; Kass, P. H.; Shahar, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
The purpose of this study was to develop a reliable and repeatable radiographic protocol for the measurement of joint angles in the standing dog, and to use this protocol to determine all standing joint angles for dogs over a wide range of body weights. The radiographic technique and the method of joint angle measurements were found to be highly repeatable, suggesting that the technique is reliable. Most joint angles did not vary between dogs of different weights. In those few instances where significant differences (p<0.05) were found, certain trends were followed and represent differences in conformation. This paper presents a complete description of the angles defining the position of the joints in a standing dog. This information is important for biomechanical studies, for clinical assessment of dogs, and for the design of surgical procedures such as arthrodesis.
Keywords: Dogs; radiographic; joint angles